Answer:
Explanation:
7) 9 - (5 - 7y) = 13 + 4y
9 - 5 + 7y = 13 + 4y
4 + 7y = 13 + 4y
7y = 13 + 4y - 4
7y - 4y = 13 - 4
3y = 9 {divide both side by 3}
y = 9/3
y= 3
12) 5(3m+4) = 3(4m+7)
5*3m + 5*4 = 3*4m + 3*7
15m +20 = 12m + 21
15m = 12m + 21 - 20
15m - 12m = 21 - 20
3m = 1
m = 1/3
14) 5(a+2) - 3(3a-5)=1
5*a + 5*2 + (-3)*3a -5 *(-3) = 1
5a + 10 - 9a + 15 = 1
5a - 9a + 10 + 15 = 1
-4a + 25 = 1
-4a = 1- 25
-4a = -24
a = -24/-4
a = 6
17) 5(v+2) + 3(v-5) = 19
5*v + 5*2 + 3*v - 5 * 3 = 19
5v + 10 + 3v - 15 =19
5v + 3v + 10 - 15 = 19
8v - 5 = 19
8v = 19 + 5
8v = 24
v= 24/8
v = 3